2022
DOI: 10.1590/fst.78621
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neuroinflammatory activity of Humulus japonicus extract and its active compound luteolin on lipopolysaccharide-induced inflammatory response in SIM-A9 microglia via NF-κB and MAPK signaling pathways

Abstract: Humulus japonicus (HJ) is administered to patients with pulmonary disease and skin disease owing to its anti-inflammatory and antioxidant effects. Lately, HJ has been shown to exert impacts on protection against neurodegenerative sickness. Nevertheless, its impacts on microglia have not been discovered in depth. As a result, anti-inflammatory impacts of HJ ethanol extract (HJE) and its active compound luteolin on lipopolysaccharide-stimulated SIM-A9 cells were investigated. The results showed that HJE luteolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…LPS is an endotoxin inducing inflammation and is used to create neurodegenerative in vitro models (Oh et al, 2021). LPS induces microglial cells activate inflammation through AKT/STAT, NF-κB, and MAPKs signaling pathways, these cells generate too many inflammatory mediators for instance NO and PGE 2 , at the same time pro-inflammatory cytokines TNF-α, IL-6, and IL-1 (Wang et al, 2021a;Wang et al, 2021b;Jung et al, 2009;Ryu et al, 2019;Zhao et al, 2019). Thus, it is significant to regulate MAPK, NF-κB, and the AKT/STAT pathways for treating neuroinflammatory diseases and controlling microglial activation can be used to treat apoptosis and inflammation in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…LPS is an endotoxin inducing inflammation and is used to create neurodegenerative in vitro models (Oh et al, 2021). LPS induces microglial cells activate inflammation through AKT/STAT, NF-κB, and MAPKs signaling pathways, these cells generate too many inflammatory mediators for instance NO and PGE 2 , at the same time pro-inflammatory cytokines TNF-α, IL-6, and IL-1 (Wang et al, 2021a;Wang et al, 2021b;Jung et al, 2009;Ryu et al, 2019;Zhao et al, 2019). Thus, it is significant to regulate MAPK, NF-κB, and the AKT/STAT pathways for treating neuroinflammatory diseases and controlling microglial activation can be used to treat apoptosis and inflammation in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…D. Li (2015) supplemented HS granules into the diet of mice with chronic bronchitis and found a reduction of cough symptoms and the amelioration of pathological damage in lung tissue. F. Wang et al (2021) investigated the anti‐inflammatory impacts of HS ethanol extract on lipopolysaccharide‐stimulated microglia. Results showed that HS ethanol extract inhibited the generation of interleukin‐1β, tumour necrosis factor‐α, nitric oxide, interleukin‐6, decreased cytoplasmic mitogen‐activated protein kinase levels and increased nuclear factor erythroid 2–related factor 2 levels in the cytoplasm and nucleus.…”
Section: Application Of Hs and Its Productsmentioning
confidence: 99%
“…supplemented HS granules into the diet of mice with chronic bronchitis and found a reduction of cough symptoms and the amelioration of pathological damage in lung tissue. F Wang et al (2021). investigated the anti-inflammatory impacts of HS ethanol extract on lipopolysaccharide-stimulated microglia.…”
mentioning
confidence: 99%
“…Chemical analysis of the extract revealed among the most abundant components luteolin-7-O-glucoside and apigenin-7-O-glucoside, molecules known to significantly inhibit the enzymatic activity of monoamine oxidase B, which plays an important role in the catabolism of neuroactive and vasoactive amines in the central nervous system and peripheral tissues (such as dopamine) [74]. The same extract was further tested to assess its anti-inflammatory impact on lipopolysaccharide-stimulated SIM-A9 cells, showing its own and luteolin's ability to inhibit, among all, the generation of interleukin-1β, tumour necrosis factor-α, nitric oxide, and interleukin-6 [75]. Recently, Kang et al (2022) demonstrated that a water extract of HJ, when orally administered (500 mg/kg/day for 3 weeks), significantly decreased β amyloid plaque deposition in the cerebral cortex and hippocampus of Alzheimer's disease (AD) mice models, also protecting against AD-related memory impairments via enhancing the cholinergic system [76].…”
Section: Humulus Japonicus/humulus Scandensmentioning
confidence: 99%